2015
DOI: 10.1175/jas-d-14-0260.1
|View full text |Cite
|
Sign up to set email alerts
|

Cold Pool and Precipitation Responses to Aerosol Loading: Modulation by Dry Layers

Abstract: The relative sensitivity of midlatitude deep convective precipitation to aerosols and midlevel dry layers has been investigated in this study using high-resolution cloud-resolving model simulations. Nine simulations, including combinations of three moisture profiles and three aerosol number concentration profiles, were performed. Because of the veering wind profile of the initial sounding, the convection splits into a left-moving storm that is multicellular in nature and a right-moving storm, a supercell, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 64 publications
2
55
1
Order By: Relevance
“…A slight caveat present in our results is that TLD (AVGHT30) is greater (higher) is environments that are slightly drier in terms of RH, in line with Wall et al . []; Grant and van den Heever [] argued that dynamical‐ and microphysical‐convective feedbacks can lead to outflow‐driven convection where the midtroposphere is relatively dry while accounting for the influence of CCN on the microphysical evolution of deep convection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A slight caveat present in our results is that TLD (AVGHT30) is greater (higher) is environments that are slightly drier in terms of RH, in line with Wall et al . []; Grant and van den Heever [] argued that dynamical‐ and microphysical‐convective feedbacks can lead to outflow‐driven convection where the midtroposphere is relatively dry while accounting for the influence of CCN on the microphysical evolution of deep convection.…”
Section: Discussionmentioning
confidence: 99%
“…Wall et al noted that relatively dry air in the middle troposphere could contribute to increased temperature lapse rates and a hostile environment for weak convection to develop in—developing plumes that overcome convective inhibition will tend to be stronger thereafter. Grant and van den Heever [] documented larger precipitation totals (and inferred stronger convection) for environments with dry layers (where relative humidity is reduced by 25–50% compared to the control environment) present near cloud base. Grant and van den Heever argued that an abundance small cloud droplets existing near cloud base can contribute to evaporative cooling via entrainment/mixing with the environment, allowing colder downdrafts to develop and stronger surface convergence to force subsequent convective development (i.e., “secondary” development that is driven by convective outflow).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wandishin et al (2008Wandishin et al ( , 2010 showed that perturbing the vertical profiles of temperature, moisture, and wind with representative analysis uncertainties could lead to vastly different MCS evolutions in idealized simulations. James and Markowski (2010) and Grant and van den Heever (2015) showed that both storm structure and accumulated precipitation are substantially altered when layers of dry air are introduced into the environment. Melhauser and Zhang (2012) used progressively smaller initial-condition perturbations to demonstrate the limitations to the practical and intrinsic predictability of a squall line, and Schumacher et al (2013) examined the influence of small differences in the prediction of an earlier convective system on the development of heavy precipitation associated with an MCV the following night.…”
Section: Introductionmentioning
confidence: 99%
“…Increased evaporation of smaller drops can result in stronger cold pool formation and enhanced secondary convection, and such increased evaporation at the cloud periphery under polluted conditions can also increase the mixing between the cloud and the environment (Khain, 2009;Lee et al, 2010). Conversely, other studies have noted that the formation of larger drops due to enhanced rain drop collision-coalescence limits evaporation and weakens the cold pool (Altaratz et al, 2008;Berg et al, 2008;Lerach et al, 2008;Storer et al, 2010;Lim et al, 2011;May et al, 2011;Morrison, 2012;Grant and Van Den Heever, 2015).…”
Section: Introductionmentioning
confidence: 99%